Filter design using multi-bragg reflectors - Ismail, Fairuz Diyana; Aziz, Muhammad Safwan; Teeka, Chat; Ali, Jalil; Yupapin, Preecha Phromphan (My University, 2012)
In this paper, we present the use of mathematical modeling of dielectric mirror known as known as Bragg reflector for optical design. A device system consists of the identical alternating layers using high and low refractive indices. Results obtained have shown that the model applications such as quarter-wavelength layers, unequal-length layers, short-pass and long-pass filters, and transmission filter design can be simulated and plotted.
Keywords: Bragg reflector; Dielectric mirror; Fabry-Perot resonator (FPR); Quarter-wavelength layers